2020
DOI: 10.1097/mlr.0000000000001353
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Follow-up Telephone Call Program on 30-Day Readmissions (FUTR-30)

Abstract: Background: Telephone call programs are a common intervention used to improve patients’ transition to outpatient care after hospital discharge. Objective: To examine the impact of a follow-up telephone call program as a readmission reduction initiative. Research Design: Pragmatic randomized controlled real-world effectiveness trial. Subjects: We enrolled and rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Following title and abstract screening, 274 full texts were retrieved. A total of 126 RCTs involving 97 408 participants met our inclusion criteria (Figure 2). The study characteristics are presented in eAppendix 3 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following title and abstract screening, 274 full texts were retrieved. A total of 126 RCTs involving 97 408 participants met our inclusion criteria (Figure 2). The study characteristics are presented in eAppendix 3 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…Across 41 studies (45 direct comparisons) involving 28 034 participants, only low-complexity interventions (OR, 0.68; 95% CI, 0.48 to 0.96) were associated decreased odds of ED visits compared with usual care (Figure 5). The P -score showed that low-complexity interventions ( P -Score, 87%) were associated with the most efficacy in reducing the odds of the ED visits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Chhabra et al studied the effect of hospital readmissions following specific orthopaedic procedures covered by Medicare and found that, after 2013, there was a significant reduction in post-surgical readmissions, suggesting that the imposition of penalties was reflected in the readmission rate. 32 In cardiology, geriatrics, neurology, pulmonology, and other specialties, there are many successful initiative programs to reduce hospital readmission, employing technologies such as telemedicine and use of messaging by applications on mobile phones 33,34 and that could be applicable in cases of hospital readmission after surgery for correction of vertebral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial including 3054 patients showed no evidence of an impact on 30day readmissions from a hospital-managed nurse follow-up telephone call program within 3 to 7 days of discharge, designed to assess understanding and provide education and assistance to support discharge plan implementation, but not provide ongoing continuity of care [11]. GeriPACT provides continuity of care and advanced open access scheduling to accommodate patient and caregiver needs.…”
Section: Discussionmentioning
confidence: 99%